Understanding Sports Policies in Indonesia: Caring for the Asian Games Legacy 2018 - Bunga Aprillia; Junita Budi Rachman (Magister Ilmu Administrasi Publik, 2021)
This research is intended to understand gender sports policies seen from a gender-sensitivity perspective. The research was based on a case study method. In-depth interviews with a number of government parties formed the cornerstone of data collection. Adopting from the conception of the Organization for Security and Co-operation in Europe (OSCE) on gender sensitivity, some of the policies do not take into account or care about gender. Thus, more precisely a policy can be genderbiased, gender blind, gender-neutral or gender-sensitive. The conception was used in analyzing the extent to which sports policy in Indonesia is gender-sensitive and its implications for the treatment Indonesia accords to the 2018 Asian Games Legacy in the field of Women in Sports. The findings of this study are categorized into three parts, inter alia, Gender equality principle; The Indonesian government's partisanship in managing female athletes; and Women in sports as soft power. The practical implication is that gender-blind conception of policies coupled with gender-neutral implementation does augur well for efforts to perpetuate the legacy of Asian Games Legacy as a powerful source of attraction that Indonesia has to offer.